Redbelly Crossing : a novel - Fox, Candice (Crooked Lane Books, 2026)
A fractured family of police detectives must solve the murder of a young woman in a small Australian town, unearthing dark secrets thought long buried. Since a violent confrontation tore apart a family five years ago, brothers and fellow cops Russell and Evan haven't spoken a word to each other. When they're both assigned to the murder of a young journalist in the tiny town of Redbelly Crossing, their paths are forced to cross again. This was supposed to be the week Russell could repair things with his teenage daughter, and instead, he has to drag her on a murderous ride into the middle of snake-infested nowhere. For Evan, this case is exactly what he needed: a high-profile investigation that will give him the chance to rebuild his career after a terrible mistake that nearly ended it. Then a dark discovery leaves Evan with only one way out: to bury the truth Russell is so determined to uncover.